DEEPFAKE DAN MASA DEPAN KEBENARAN: IMPLIKASI ETIS DAN SOSIAL - Widjaja, Gunawan (Berajah Journal, 2025)
The development of deepfake technology powered by artificial intelligence has brought significant changes to the digital communication landscape and the perception of truth. Deepfakes enable the creation of highly realistic, yet entirely fake, visual and audio content, blurring the line between fact and fabrication. This study uses a literature review method to analyze the ethical and social implications of the deepfake phenomenon, particularly regarding the future of truth. The results show that deepfakes pose serious challenges in the form of privacy violations, the spread of disinformation, a decline in public trust, and the potential for social polarization and threats to democracy. On the other hand, this technology also offers innovative opportunities in the fields of entertainment, education, and health if used responsibly. Therefore, adaptive regulations, the development of detection technologies, and increased digital literacy are needed to minimize the risks and maximize the benefits of deepfakes for society.